2008
DOI: 10.1073/pnas.0809882105
|View full text |Cite
|
Sign up to set email alerts
|

Phage φ29 and Nf terminal protein-priming domain specifies the internal template nucleotide to initiate DNA replication

Abstract: Bacteriophages 29 and Nf from Bacillus subtilis start replication of their linear genome at both DNA ends by a protein-primed mechanism, by which the DNA polymerase, in a template-instructed reaction, adds 5 -dAMP to a molecule of terminal protein (TP) to form the initiation product TP-dAMP. Mutational analysis of the 3 terminal thymines of the Nf DNA end indicated that initiation of Nf DNA replication is directed by the third thymine on the template, the recovery of the 2 terminal nucleotides mainly occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
(47 reference statements)
0
20
0
Order By: Relevance
“…The Φ29-related phage Nf and the Streptococcus pneumoniae phage Cp-1 initiate replication at the 3΄ third nucleotide of the template ( 3΄ TTT) (23,24). E. coli phage PRD1 initiates at the 3΄ fourth nucleotide ( 3΄ CCCC) (25).…”
Section: Resultsmentioning
confidence: 99%
“…The Φ29-related phage Nf and the Streptococcus pneumoniae phage Cp-1 initiate replication at the 3΄ third nucleotide of the template ( 3΄ TTT) (23,24). E. coli phage PRD1 initiates at the 3΄ fourth nucleotide ( 3΄ CCCC) (25).…”
Section: Resultsmentioning
confidence: 99%
“…Previous assays showed that the priming domain is the main structural determinant that dictates the internal 3Ј nucleotide used as template during initiation (21). Here, we have analyzed the role of the aromatic residue Phe-230 of the TP priming loop, proximal to the priming Ser-232.…”
Section: Discussionmentioning
confidence: 99%
“…assays with chimerical TPs indicated that the priming domain is responsible for placing the templating nucleotide at the polymerization active site during initiation (21). The TP priming domain (residues 173-266) is comprised of a four-helix bundle structure, the priming loop (residues 227-233) being located between the last and penultimate ␣ helixes of the domain (19).…”
Section: Role Of the Priming Loop Aromatic Residue Phe-230 In Positiomentioning
confidence: 99%
See 1 more Smart Citation
“…the priming loop (Longás et al, 2008). Then, after a transition step, the DNAP dissociates, and the elongation continues until replication of the nascent DNA strand is completed, thanks to the high processivity of the DNAP and its intrinsic strand displacement activity.…”
Section: Alternative Protein-primed Genome Replication Mechanismsmentioning
confidence: 99%